The Civic Engagement Strategy of the Kampoeng Baca Pelangi Community In Fulfillment Of Educational Basic Services for Children Victims of the Lombok Earthquake - Ahmad Hudori; Dewi Gunawati; Triana Rejekiningsih (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This article discusses the Kampoeng Baca Pelangi community in an effort to fulfill basic education services for children affected by the Lombok earthquake. The earthquake has resulted in a long period of school closures. Earthquakes have been responsible for child deaths, as well as physical and psychological injuries to children and disruption of education delivery services. The purpose of this study was to find out the strategy for the involvement of Kampoeng Baca Pelangi, the obstacles felt by Kampoeng Baca Pelangi and the solutions implemented to overcome obstacles in fulfilling basic education services for children affected by the Lombok earthquake. Data were collected by interview, observation and documentation. The results of this study are: Kampoeng Baca Pelangi's involvement strategy in fulfilling basic education services for children affected by the Lombok earthquake is through the implementation of various programs, including tutoring. The perceived obstacles consist of internal and external factors, internal factors consist of the lack of community operational funds, tutors are still limited; while the external factor is the emergence of an unfavorable perception of Kampoeng Baca Pelangi. Solutions applied: internal factors held dues between the management of Kampoeng Baca Pelangi, sold Kampoeng Baca Pelangi merchandise, held deliberations between the management and the community. Meanwhile, for external factors, Kampoeng Baca Pelangi focused on working until it finally succeeded in producing its first music album that can be enjoyed on various digital music platforms.